2014
DOI: 10.1182/blood-2013-02-486688
|View full text |Cite
|
Sign up to set email alerts
|

Functions of flt3 in zebrafish hematopoiesis and its relevance to human acute myeloid leukemia

Abstract: Key Points• Zebrafish flt3 plays an important role in the initiation of definitive hematopoietic stem cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
49
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 50 publications
2
49
1
Order By: Relevance
“…As a molecule controlling important cellular processes such as the growth, proliferation and survival of HSPCs, FLT3 is involved in the pathogenesis of AML. 2528 We therefore investigated the human CBL-FLT3 pathway in the 293T cell line because no appropriate agents were available for similar studies in zebrafish. 293T cells were transiently transfected to express FLT3 with WT c-CBL or c-CBL-H398Y.…”
Section: Resultsmentioning
confidence: 99%
“…As a molecule controlling important cellular processes such as the growth, proliferation and survival of HSPCs, FLT3 is involved in the pathogenesis of AML. 2528 We therefore investigated the human CBL-FLT3 pathway in the 293T cell line because no appropriate agents were available for similar studies in zebrafish. 293T cells were transiently transfected to express FLT3 with WT c-CBL or c-CBL-H398Y.…”
Section: Resultsmentioning
confidence: 99%
“…34 Quantitative reverse-transcription PCR (qRT-PCR) was performed using the StepOnePlus Real-time PCR system (Applied Biosystems Inc.) with a SYBR Green master mix. Analysis was performed in triplicate by the 2 2DDC(T) method and b-actin was used as the housekeeping gene.…”
Section: Qrt-pcrmentioning
confidence: 99%
“…We concluded that FLT3-ITD-expressing myeloid cells arose in the KM, and immature blast cells progressively infiltrated the KM before being circulated into the PB. Recently, He et al 15 reported that ubiquitous expression of FLT3 had important roles in primitive and definitive hematopoiesis during the embryonic development of zebrafish. They also demonstrated that expressing human FLT3-ITD in zebrafish embryos resulted in myeloid cells expansion and clustering.…”
mentioning
confidence: 99%
“…They also demonstrated that expressing human FLT3-ITD in zebrafish embryos resulted in myeloid cells expansion and clustering. 15 However, they didn't examine the phenotype of FLT3-ITD expression in adult zebrafish. In the present study, we expressed the FLT3-ITD in spi-1-positive cells and demonstrated some leukemia phenotype at the age of 9 months.…”
mentioning
confidence: 99%